Radiotherapy and Cytokine Storm: Risk and Mechanism - Zhang, Chen; Liang, Zhenzhen; Ma, Shumei; Liu, Xiaodong (Frontiers in Oncology, 2021)
Radiotherapy (RT) shows advantages as one of the most important precise therapy strategies for cancer treatment, especially high-dose hypofractionated RT which is widely used in clinical applications due to the protection of local anatomical structure and relatively mild impairment. With the increase of single dose, ranging from 2~20 Gy, and the decrease of fractionation, the question that if there is any uniform standard of dose limits for different therapeutic regimens attracts more and more attention, and the potential adverse effects of higher dose radiation have not been elucidated. In this study, the immunological adverse responses induced by radiation, especially the cytokine storm and the underlying mechanisms such as DAMPs release, pro-inflammatory cytokine secretion and cGAS-STING pathway activation, will be elucidated, which contributes to achieving optimal hypofractionated RT regimen, improving the killing of cancer cells and avoiding the severe side effects.